Mobile multimedia communications : 6th International ICST Conference, MOBIMEDIA 2010, Lisbon, Portugal, September 6-8, 2010. Revised Selected Papers - Tafazolli, Rahim; Verikoukis, Christos; Rodriguez, Jonathan (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International ICST Conference on Mobile Multimedia Communications (MOBIMEDIA 2010) held in Lisbon, Portugal, in September 2010, which was accompanied by the First International Workshop on Cognitive Radio and Cooperative Strategies for POWER Saving (C2POWER 2010), the Workshop on Impact of Scalable Video Coding on Multimedia Provisioning (SVCVision 2010), and the First International Workshop on Energy-efficient and Reconfigurable Transceivers (EERT 2010). The 59 revised full papers presented were carefully reviewed and selected from numerous submissions and are organized in topical sections on advanced techniques for video transmission; multimedia distribution; modelling of wireless systems; cellular networks; mobility concepts for IMT-advances (MOBILIA); media independent handovers (MIH-4-MEDIA); and IP-based emergency applications and services for next generation networks (PEACE).